Identification of Genes whose mRNAs are Subjected to Alternative Splicing by Endonuclease EndoG Action in Human and Murine CD4+ T Lymphocytes - Zhdanov, D.D.; Novachly, N.S.; Pokrovskaya, M.V.; Aleksandrova, S.S.; Kabardokov, T.A.; Sokolov, N.N. (Biomedical Chemistry: Research and Methods, 2020)
The aim of this work was to identify genes whose mRNAs were subjected to alternative splicing by apoptotic endonuclease EndoG in CD4+ Т lymphocytes from healthy humans, mice, and rats. In order to induce EndoG, lymphocytes were transfected with an EndoG-containing plasmid, or a control pGFP plasmid, or were incubated with cisplatin. Efficiency of transfection, number of cells with DNA damages and the level of EndoG expression have been monitored. Total cell mRNA has been sequenced and the changes in proportion of splice variants of genes were analyzed. The changes in the proportion of 28 mRNA splice variants have been identified in human and murine lymphocytes in both transfected with EndoG gene or incubated with cisplatin. Thus, EndoG can be considered as a potent modulator of alternative splicing of mRNA of identified genes.